threatening a teacher - Hassan, Tuka Younis (Journal of the Faculty of Medicine Baghdad, 2021)
Abstract Background: Threatening teachers increases teacher stress and impairs emotional well-being. There are many reasons for violence against teachers. There are communication errors and conceptual differences in applying the rules that emphasizes corporal punishment rather than persuasive punishment. Also, it is related to a parent complaint that expresses Parents’ belief in the education their child received in school is getting weaker. In addition to the incompetence that teachers must implement, like personal, social and professional aspects that make students offend teachers. Threatening someone considered as physical aggression. Aggression is any behavior intended to harm another person that wishes to avoid such harm High rates of aggression were reported recently in Iraq, especially after wars. Some studies have shown that students, whose friends engage in negative activities such as dropping out of school and have lower academic performance, may engage in aggressive activities toward teachers and/or other students. Objectives: To estimate the prevalence of students’ aggressive act towards teachers. Methodology: A cross-sectional study was carried out in Al-Sadr city in Baghdad. A total of 720 adolescent secondary schools students from both genders were included in the study. They were selected by multistage random sampling. Their age was ranged from 13-21 years. Data was collected from 1st of February 2019 to 30 of April 2019 through a self-reported questionnaire (Aggression-Problem Behavior Frequency Scale). Results: The mean age of participants was 16.2±2.04 years. Of all participants, 84.3% were assessed to be aggressive. There was a significant difference between aggressive act (threatening a teacher) and sex, school type, grade, history of absence from school and employed mother,(P=0.038, 0.009, 0.0001,p= 0.02 and p=0.018, respectively). 10% of male threatening a teacher. Conclusion: A high prevalence of aggression among students was found. Threatening a teacher was dominant among male students, intermediate schools, 4th grade, students with history of absence from school, and not employed mother.